Lymphangioma of the Mesentery: Case Report and Review of the Literature - Gendvilaitė, Neda; Drachneris, Julius; Poškus, Tomas (Acta medica Lituanica, 2021)
Background: Lymphangioma of the mesentery is a rare benign condition. Lymphangioma usually occurs in children during first few years of life most likely because of congenital abnormality of the lymphatic system. It may also be caused by trauma, lymphatic obstruction, surgery, inflammatory process, or radiotherapy. Lymphangioma of the mesentery represents less than 1% of all lymphangiomas and about 70% of abdominal lymphangiomas.Case presentation: We report the case of the 42-year-old woman who was diagnosed with the lymphangioma. Laparotomy was performed. A cystic lymph-filled tumor of about 12 cm in diameter was removed from the ileum mesentery. Conclusions:  Lymphangioma of the mesentery is a rare condition. Despite its benign nature, it can cause serious complications if not treated. Ultrasound and CT are used for detection of lymphangioma. It is important to surgically remove the lymphangiomas even in the absence of symptoms.
Keywords: lymphangioma; lymphatic system; mesenterium